The seroepidemiology of herpes simplex virus type 1 and 2 in Europe. Issue 3 (28th May 2004) - Pebody, R G; Andrews, N; Brown, D; Gopal, R; de Melker, H; François, G; Gatcheva, N; Hellenbrand, W; Jokinen, S; Klavs, I; Kojouharova, M; Kortbeek, T; et al.
Abstract : Objectives: To describe the seroepidemiology of herpes simplex virus (HSV) types 1 and 2 in the general populations of eight European countries to better understand recent reported changes in disease epidemiology. Methods: Belgium, Bulgaria, Czech Republic, England and Wales, Finland, Germany, Netherlands, and Slovenia conducted national cross sectional serological surveys for HSV-1 and HSV-2 between 1989 and 2000. Survey sizes ranged from 3000 to 7166 sera. External quality control was ensured through reference panel testing. Results: Large intercountry and intracountry differences in HSV-1 and HSV-2 seroprevalence were observed. Age standardised HSV-1 seroprevalence ranged from 52% in Finland, to 57% in the Netherlands, 67% in Belgium, 81% in Czech Republic, and 84% in Bulgaria. Age standardised (>12 years) HSV-2 seroprevalence ranged from 24% in Bulgaria, to 14% in Germany, 13% in Finland, 11% in Belgium, 9% in Netherlands, 6% in Czech Republic, and 4% in England and Wales. In all countries, probability of seropositivity for both infections increased with age. A large proportion of teenagers and young adults remain HSV-1 susceptible particularly in northern Europe. Women were significantly more likely to be HSV-2 seropositive in six of seven (p<0.05) countries and HSV-1 seropositive in four of seven (p<0.05) countries, particularly in northern Europe. No significant evidence of a protective role of HSV-1 for HSV-2 infection was found adjusting for age and sex (p<0.05). Conclusions: There is large variation in the seroepidemiology of HSV-1 and HSV-2 across Europe. The observation that a significant proportion of adolescents are now HSV-1 susceptible may have implications for transmission and clinical presentation of HSV-1 and HSV-2.